Assembly of donor–acceptor hybrid heterostructures based on iodoplumbates and viologen coordination polymers. Issue 35 (24th August 2017) - Liu, Jian-Jun; Shan, Yue-Bin; Dai, Wen-Xin; Huang, Chang-Cang; Lin, Mei-Jin
Abstract : Two D–A hybrid heterostructures have been formed by the insertion of electron-rich iodoplumbates into viologen coordination polymers, which exhibit highly effcient photocatalytic degradation RhB under visible light irradiation. Abstract : The insertion of electron-rich iodoplumbate nanowires and nanolayers into layered electron-deficient metal-viologen frameworks leads to two donor–acceptor hybrid structures, respectively, which exhibit interesting semiconductor behaviors. Due to the bicontinuous donor and acceptor components, both of them exhibit highly efficient photocatalytic degradation activities over organic dyes under visible light irradiation compared to those of other iodoplumbate hybrid materials.